Method for manufacturing recycled polyester fiber using a melt extrusion device equipped with an extrusion nozzle unit
Patent Information
- Application Number
- KR1020250025421
- Authority / Receiving Office
- KR · KR
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-02-26
- Publication Date
- 2026-09-02
Smart Images

Figure PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a method for manufacturing recycled polyester fibers using a melt extrusion device equipped with an extrusion nozzle unit. Background Technology
[0002] As the use of plastics and synthetic fibers increases, recycling technology for waste management and solving environmental problems is establishing itself as an important research field, and in particular, processes for producing new polyester fibers by recycling waste fibers and waste plastics are continuously being developed.
[0003] Generally, polyester fibers are manufactured based on polyethylene terephthalate (PET). Although PET is widely used in various fields such as beverage containers, packaging materials, clothing, and industrial fibers, an effective recycling process is essential because it is difficult to naturally decompose when discarded after use.
[0004] Conventional polyester fiber recycling processes are broadly classified into mechanical recycling and chemical recycling. Mechanical recycling involves washing and crushing waste fibers or plastics to re-spinning them, while chemical recycling generally involves converting PET into raw material monomers through hydrolysis or depolymerization.
[0005] Among these, the mechanical recycling process is widely used industrially due to its relatively low cost and simplicity; however, it has the disadvantage that the strength and durability of the recycled fibers are lower than those of the raw fibers, as polymer chains shorten and physical properties deteriorate during the repetitive melting and extrusion processes.
[0006] Alternatively, chemical recycling processes can regenerate high-purity polymers by reducing PET to raw monomers, making it easier to maintain quality compared to mechanical recycling; however, commercialization is difficult due to the high costs associated with the hydrolysis and depolymerization processes, which consume a significant amount of energy and chemicals.
[0007] In such conventional recycling processes, pretreatment steps such as washing, impurity removal, and de-dyeing are essential to increase the purity of polyester raw materials. In particular, since waste fibers recovered from clothing and fabrics contain various dyes and coating materials, completely removing them is a critical factor in ensuring quality.
[0008] Accordingly, in order to improve the quality of recycled polyester fibers, research is currently being conducted on technologies that improve physical properties by mixing additives or reinforcing materials into existing processes.
[0009] In this regard, prior art documents regarding prior art provided to offer a method for manufacturing reinforcing fibers for plastic-reinforced concrete by utilizing polymer waste materials such as waste fibers and waste plastics in order to lower the manufacturing cost of plastic-reinforced concrete include Korean Registered Patent Publication No. 10-0521426, "Method for manufacturing reinforcing plastic fibers for plastic-reinforced concrete using a composite material of waste fibers and waste plastics" (hereinafter referred to as "prior art").
[0010] However, existing technologies for manufacturing recycled polyester fibers using polymer waste materials, such as waste fibers and waste plastics, including conventional technologies, have limitations such as reduced fiber quality due to limitations in removing impurities and dyes, decreased mechanical properties caused by the shortening of polymer chains during the melting and extrusion processes, and reduced production efficiency due to nozzle clogging and difficulties in forming uniform fibers during continuous production. The problem to be solved
[0011] The present invention was created to solve the above problems, and the objective of the present invention is to provide a method for manufacturing recycled polyester fibers that can effectively recycle waste fibers and waste plastics to produce polyester fibers of uniform quality, ensure uniformity of fiber formation during the melt extrusion process, improve continuous productivity, and improve fiber strength and durability. means of solving the problem
[0012] To achieve the above objective, a method for manufacturing recycled polyester fibers using a melt extrusion device equipped with an extrusion nozzle unit of the present invention comprises: Step A, which involves treating waste fibers and waste plastics that have been sorted, washed, and crushed, and then treating them with decolorization followed by washing and drying; and Step B, which involves melt extruding the treatment target that has undergone decolorization followed by washing and drying in Step A under conditions of a temperature of 250°C to 300°C and a pressure of 150 Bar to 250 Bar, and then pelletizing the resulting strand into a chip form to prepare recycled polyester chips. and Step C, wherein the recycled polyester chips prepared through Step B are dried, then fed into a melt extrusion device, and the polymer, converted into a molten state through heat treatment under conditions of a temperature of 270°C to 290°C and a pressure of 150 Bar to 250 Bar, is fed into an extrusion nozzle unit provided in the melt extrusion device, undergoes a plurality of filtering treatments, and is spun into a thread form; wherein the extrusion nozzle unit provided in the melt extrusion device used through Step C comprises: a nozzle body having a predetermined installation space inside and an inlet port at the top for feeding the molten polymer; a first filter section disposed on the top of the nozzle body; and a plate-shaped first nozzle section disposed so that the bottom and top surfaces of the first filter section are in contact, and having a plurality of first micro-movement holes open vertically to guide the downward movement of the polymer passing through the first filter section. Sand having a particle size of 200μm to 400μm, filled between the upper part of the first filter section within the installation space and the lower part of the inlet provided in the exposed body; a second filter section arranged so that the lower and upper parts of the first nozzle section are in contact, and having a filter hole size smaller and a larger number of meshes compared to the first filter section;A plate-shaped second nozzle part arranged so that the lower and upper surfaces of the second filter part are in contact, and having a plurality of second micro-movement holes open vertically to guide the downward movement of the polymer passing through the second filter part; a third filter part arranged so that the lower and upper surfaces of the second nozzle part are in contact, and having a filter hole size smaller and a mesh count larger than that of the second filter part; and a plate-shaped third nozzle part arranged so that the lower and upper surfaces of the third filter part are in contact, and having a plurality of third micro-movement holes open vertically to guide the downward movement of the polymer passing through the third filter part; wherein the third nozzle part is provided in the shape of a tapered truncated cone with a cross-sectional area that decreases as it extends downward.
[0013] In addition, on the inner walls of the plurality of third micro-moving holes provided in the third nozzle part, a Diamond-Like Carbon (DLC) coating treatment is performed using Chemical Vapor Deposition (CVD) at a temperature of 250°C to 450°C and under vacuum conditions, so that a third coating film having a thickness of 1 μm to 3 μm is formed.
[0014] Here, the first filter portion has a filter hole size of 200 μm to 400 μm and the filter holes are formed to a size of 50 mesh to 80 mesh, and the first nozzle portion is provided with a plurality of first micro-moving holes having a diameter of 0.5 mm to 1.0 mm, and a coating treatment using a first coating composition comprising 20 to 35 parts by weight of polytetrafluoroethylene (PTFE), 8 to 13 parts by weight of carbon nanotube (CNT), 10 to 14 parts by weight of hexafluoropropylene (HFP), 15 to 18 parts by weight of nano silica (Nano-SiO2), and 5 to 7 parts by weight of poly(hexamethylene dodecanediamide) is performed on the inner walls of the plurality of first micro-moving holes provided in the first nozzle portion, so as to form a diameter of 2 μm to A first coating film having a thickness of 4 μm is formed.
[0015] Next, the second filter portion has a filter hole size of 120 μm to 140 μm and the filter hole is formed to a size of 80 mesh to 150 mesh, and the second nozzle portion is provided with a plurality of second micro-moving holes having a diameter of 0.2 mm to 0.5 mm, and a coating treatment using a second coating composition comprising 55 to 60 parts by weight of aluminum oxide, 15 to 19 parts by weight of silicon carbide; 7 to 9 parts by weight of yttria-stabilized zirconia (YSZ); and 12 to 14 parts by weight of poly(dimethylsiloxane) is performed on the inner walls of the plurality of second micro-moving holes provided in the second nozzle portion to form a second coating film having a thickness of 50 μm to 70 μm.
[0016] In addition, the third filter section has a filter hole size of 20 μm to 50 μm, and the filter hole is formed to a size of 300 mesh to 500 mesh, and the third nozzle section is provided with a plurality of third fine moving holes having a diameter of 0.2 mm to 0.5 mm.
[0017] And the above method for manufacturing recycled polyester fibers further includes step D, which involves cooling the polymer extruded in the form of a thread through the extrusion nozzle unit in step C to a temperature of 15°C to 25°C and then stretching it at a draw ratio of 1.5 to 3.5 to produce recycled polyester fibers. Effects of the invention
[0018] According to the present invention, the following effects are achieved.
[0019] First, in the process of manufacturing polyester chips by recycling waste fibers and waste plastics, by including a process of pelletizing after melt extrusion under conditions of a temperature of 250°C to 300°C and a pressure of 150 Bar to 250 Bar, the shortening of polymer chains can be minimized and the mechanical properties of the recycled polyester can be improved.
[0020] Second, in the present invention, by applying a technology that extrudes a molten polymer through a plurality of filtering steps via an extrusion nozzle unit under conditions of a temperature of 270°C to 290°C and a pressure of 150 Bar to 250 Bar, impurities can be effectively removed and uniform fiber spinning is possible, and high-quality recycled polyester fibers can be produced.
[0021] Third, by providing a polymer sand layer with a particle size of 200 μm to 400 μm inside the extrusion nozzle unit, the polymer flow can be uniformly controlled and fine impurities can be additionally removed, thereby reducing nozzle clogging compared to conventional filtering systems and improving continuous productivity.
[0022] Fourth, the extrusion nozzle unit of the present invention includes a multi-stage filter and nozzle structure, and has a structure in which the size of the filter holes decreases and the number of meshes increases from the first filter section to the third filter section, thereby performing stepwise precision filtering to maximize the uniformity of fiber spinning.
[0023] Fifth, by applying a Diamond-Like Carbon (DLC) coating using chemical vapor deposition (CVD) at a temperature of 250°C to 450°C and under vacuum conditions to the inner wall of the internal micro-movement hole of the third nozzle part, the coefficient of friction is lowered and wear resistance is increased, thereby minimizing breakage and improving the continuous productivity of the fiber.
[0024] Sixth, a polytetrafluoroethylene (PTFE)-based superhydrophobic coating and an alumina-based heat-resistant ceramic coating are applied to the inner walls of the micro-movement holes of the first nozzle section and the second nozzle section, respectively, thereby preventing polymer adhesion and increasing thermal stability, which can ensure the reliability of the spinning process.
[0025] Seventh, by including a process of cooling the spun polymer fiber to a temperature of 15°C to 25°C and then stretching it with a draw ratio of 1.5 to 3.5, the crystallization of the fiber is optimized, and tensile strength and durability are improved, thereby improving the quality compared to existing recycled fibers.
[0026] Eighth, by optimizing the structure and coating technology of the extrusion nozzle unit, the present invention can effectively solve problems such as nozzle clogging, uneven spinning, and reduced fiber strength that occur in existing recycled polyester fiber manufacturing methods, and can maximize industrial applicability. Brief explanation of the drawing
[0027] FIG. 1 is a flowchart illustrating a method for manufacturing recycled polyester fibers using a melt extrusion device equipped with an extrusion nozzle unit according to the present invention. FIG. 2 is a drawing illustrating the installation configuration of an extrusion nozzle unit according to detailed configurations provided in a melt extrusion device used in a method for manufacturing recycled polyester fibers according to the present invention. Specific details for implementing the invention
[0028] Preferred embodiments of the present invention will be described in more detail with reference to the attached drawings, provided that technical details that are already well known are omitted or compressed for the sake of brevity.
[0029] 1. Description of the method for manufacturing recycled polyester fibers
[0030] The process of manufacturing recycled polyester fibers using a melt extrusion device (100) equipped with an extrusion nozzle unit (120) of the present invention will be explained in detail below with reference to the flowchart of FIG. 1.
[0031] (1) First preprocessing step<S110, A단계>
[0032] In this stage, waste fibers and waste plastics that have been sorted, washed, and crushed are treated, and a process of decolorization followed by washing and drying is carried out.
[0033] First, waste fibers and waste plastics are primarily classified into fabrics, PET bottles, and other plastics through mechanical sorting, and then surface contaminants and attached foreign substances are removed through chemical washing.
[0034] In the subsequent washing process, an alkaline aqueous solution (NaOH or KOH) and a surfactant are used to dissolve and remove impurities such as oil, wax, and adhesives, and a high-temperature rinsing process is added to minimize residual contaminants.
[0035] In addition, in the de-dyeing process of waste fibers, the existing dye is removed by destroying the disperse dye using an oxidizing agent (hydrogen peroxide, H2O2) or a reducing agent (hydrosulfite, Na2S2O4), or thiourea dioxide (TUDO) and caustic soda (NaOH), and the process is carried out by adding a catalyst to increase the reaction rate as needed.
[0036] In this process, the temperature (50°C to 80°C) and pH (8 to 10) are controlled to prevent the decomposition of the fibers while maximizing the dye removal rate.
[0037] After the dedyeing treatment, a neutralization process is performed to remove residual by-products generated by chemical reactions, and multi-stage washing and drying treatments are carried out to ensure stability in the continuous process.
[0038] In addition, after washing, drying is performed using a hot-air drying or vacuum drying method to reduce the moisture content to 1% or less, thereby preventing the formation of moisture bubbles that may occur during melt extrusion in subsequent processes.
[0039] (2) Second preprocessing step<S120, B단계>
[0040] In this step, a process is carried out to prepare recycled polyester chips by pelletizing the strands produced by melt-extruding the target, which has undergone de-dyeing treatment, washing, and drying treatment through the first pretreatment step (S110) performed earlier, under conditions of a temperature of 250°C to 300°C and a pressure of 150 Bar to 250 Bar.
[0041] To this end, the product to be treated undergoes additional pre-drying treatment to ensure fluidity suitable for the extrusion process, and typically undergoes vacuum drying or dehumidification at a temperature of 80°C to 120°C for 46 hours to control the moisture content to 0.5% or less.
[0042] This prevents the formation of bubbles that may occur during melt extrusion and maintains the viscosity of the polymer, thereby enabling the formation of uniform strands.
[0043] Subsequently, to optimize the quality of recycled polyester chips, the heating temperature, screw rotation speed, and extrusion speed are precisely controlled in the melt extrusion process.
[0044] Specifically, the screw rotation speed is controlled within the range of 50 rpm to 150 rpm, and the residence time of the melt extruder is set to within 25 minutes to prevent thermal decomposition of the polymer and deterioration of physical properties.
[0045] In addition, melt extrusion is carried out under conditions of a temperature of 250°C to 300°C and a pressure of 150 Bar to 250 Bar, which is to stably melt and extrude polyethylene terephthalate (PET)-based polyester, because at temperatures below 250°C, sufficient fluidity is not secured, so extrusion does not proceed smoothly, and at temperatures above 300°C, there is a risk that thermal degradation will be accelerated.
[0046] In addition, pressure conditions of 150 Bar to 250 Bar during polymer melt extrusion are essential for effectively removing impurities while maintaining polymer fluidity and forming uniform strands, because if the pressure is less than 150 Bar, the fluidity of the molten polymer is insufficient, making it difficult to form uniform strands, and conversely, if it exceeds 250 Bar, excessive pressure can cause changes in viscosity and the formation of microbubbles.
[0047] In this way, the melt-extruded strand is cut into a certain length (2 mm to 5 mm) and pelletized into chip form, and rapid cooling is performed using cooling water or air cooling to ensure uniformity of chip size.
[0048] Afterward, the material undergoes a screening process using a vibrating sieve or cyclone filter to remove dust and fine chips, followed by storage and transportation for subsequent processes.
[0049] (3) Melt extrusion processing step<S130, C단계>
[0050] In this step, the recycled polyester chips prepared through the previously performed second pretreatment step (S120) are dried and then fed into a melt extrusion device. The polymer, which is converted into a molten state through heat treatment under conditions of a temperature of 270°C to 290°C and a pressure of 150 Bar to 250 Bar, is fed into an extrusion nozzle unit (120) provided in the melt extrusion device (100), undergoes a plurality of filtering treatments, and then is spun into a thread form.
[0051] Here, the melt extrusion device (100) includes a melt treatment unit (110) that converts hay-treated recycled polyester chips into a molten state through heat treatment under conditions of a temperature of 270°C to 290°C and a pressure of 150 Bar to 250 Bar, and an extrusion nozzle unit (120) that filters the molten polymer and then spins it into a thread form.
[0052] First, the melting unit (110) is composed of a recycled polyester chip supply system, a preheating zone, a melting zone, and a mixing and pressurizing zone, and is designed to extrude a uniform molten polymer while maintaining a continuous process flow.
[0053] In order for melt extrusion to be performed stably, recycled polyester chips must be sufficiently dried in advance, and it is essential to reduce residual moisture to 0.5% or less. Therefore, the drying system applies vacuum drying or hot-air drying methods, and the drying temperature is maintained in the range of 80°C to 120°C for 46 hours to effectively remove moisture inside the polymer.
[0054] This is because if moisture remains, bubbles and fine impurities may form during the melting process, potentially degrading the quality of the final spun fiber; therefore, strict control is implemented during the drying stage.
[0055] The dried polyester chips are transferred to the melting unit (110) through a supply hopper, and the hopper includes an auger mixer to ensure that the chips are fed uniformly.
[0056] Next, the polyester chips pass through a preheating zone that is gradually heated before reaching a target temperature of 270°C to 290°C so that they can melt. In the preheating zone, to prevent thermal degradation and viscosity reduction that may occur when the chips are suddenly exposed to high temperatures, a first preheating is performed at an intermediate temperature of 150°C to 200°C, and the temperature is gradually increased by controlling the ramp rate.
[0057] These preheating sections include a heater element and a thermocouple sensor, and maintain a constant temperature while monitoring process variables in real time.
[0058] In addition, a rotary agitator or a vibrating conveyor may be included to help with uniform heat transfer of recycled polyester chips.
[0059] Next, the preheated polyester chips are converted into a complete liquid polymer in the melting zone, and uniform melting occurs in the range of 270°C to 290°C. In this section, the chips are moved using a forcibly compressed extruder screw, and the solid chips are gradually converted into a liquid state through compression and shear action.
[0060] Specifically, the interior of the molten section is composed of multi-stage heating zones, the front zone maintains a relatively low temperature (250°C to 270°C) to gradually transfer heat, and the rear zone maintains a high temperature (270°C to 290°C) for final melting.
[0061] In this process, a liquid polymer with constant viscosity can be formed through a combination of screw compression and heat transfer.
[0062] The completely melted polymer is moved to the Mixing & Pressurizing Zone to undergo a homogenization process. At this stage, a constant pressure (150 Bar to 250 Bar) is applied to remove residual microbubbles and impurities and to maintain optimal viscosity.
[0063] Next, the mixing section includes a multi-stage static mixer to enable precise flow rate control, and uses a high-pressure gear pump or piston pump to maintain constant viscosity through pressure increase.
[0064] If the pressure is not maintained constant during this process, the polymer fluidity becomes uneven and the fiber quality may deteriorate during spinning; therefore, real-time feedback control using a pressure sensor is implemented.
[0065] In addition, the mixing section may include a vacuum degassing system for removing oxygen and impurities, thereby preventing polymer oxidation and post-spinning yellowing.
[0066] Finally, the polymer, having undergone mixing and pressurization, moves to a stabilization zone just before extrusion to perform final viscosity adjustment. In this zone, optimal spinning conditions are secured by finely adjusting temperature and pressure while maintaining a uniform polymer flow.
[0067] In particular, viscosity control is achieved by controlling the dwell time at high temperatures, and generally, the molecular alignment of the polymer is stabilized by maintaining a constant temperature and pressure for 2 to 5 minutes.
[0068] Specifically, the viscosity of the molten polymer is controlled to maintain a range of 0.6 dL / g to 0.7 dL / g based on intrinsic viscosity (IV), and this value serves as an important factor in securing optimal strength and elongation during fiber spinning.
[0069] If this IV value drops below 0.6 dL / g, the mechanical strength of the fiber decreases, and conversely, if it exceeds 0.7 dL / g, the viscosity increases, increasing the likelihood of breakage during the spinning process.
[0070] To this end, the polymer dwell time during melt extrusion is maintained within 25 minutes to prevent a decrease in IV value due to thermal decomposition, and multi-stage precision pressure control (150 Bar to 250 Bar) is applied to ensure viscosity uniformity within the molten section, and a high-pressure gear pump and a precision filtering system are applied immediately before extrusion to minimize viscosity changes and maintain flow uniformity.
[0071] In addition, if the temperature is non-uniform at this stage, nozzle clogging or spinning defects may occur during the filtering process, so it is essential to maintain optimal conditions.
[0072] The molten polymer, prepared by passing the recycled polyester chips dried in this manner through the melt extrusion device (100), is fed into the extrusion nozzle unit (120), undergoes multiple filtering processes, and is then spun into a thread form. Most importantly, various effects are improved through the specific configuration characteristics of the extrusion nozzle unit (120).
[0073] In this regard, the extrusion nozzle unit (120) is formed by using a nozzle body (121a, 121b) as a basic housing, which has a predetermined installation space (121T) inside and an inlet (121H) for introducing a molten polymer at the top, and accommodating a first filter section (122) to a third filter section (127), a first nozzle section (123) to a third nozzle section (128), and a sand (124) layer in the internal installation space (121T) as shown in FIG. 2.
[0074] First, the nozzle body (121a, 121b) includes an upper body part (121a) having an inlet (121H) at the top and a lower cover part (121b) which is connected to the lower part of the upper body part (121a) to create a closed space inside and has an outlet (121b) that is open vertically so that a polymer passing through both the filter and the nozzle can be emitted from the bottom.
[0075] Next, the first filter section (122) is positioned at the top of the internal installation space (121T) of the nozzle body (121a, 121b) and corresponds to a stainless steel (STS 316L) mesh filter that removes large foreign substances (solid impurities, aggregated polymer clumps).
[0076] In particular, the first filter section (122) is made of high-strength stainless steel (STS 316L) so as not to deform even in a high-pressure environment of 150 Bar to 250 Bar, and has excellent heat resistance and chemical resistance, so it can maintain structural stability even when in contact with molten polymer for a long time.
[0077] Specifically, the first filter section (122) has a filter hole size of 200 μm to 400 μm, and the filter hole is formed to be 50 mesh to 80 mesh, making it effective for removing large aggregates and enabling filtering without reducing flow rate.
[0078] And prior to this, sand (124) having a particle size of 200 μm to 400 μm is filled between the upper part of the first filter section (122) and the lower part of the inlet (121H) provided in the exposure body (121a, 121b) based on the internal installation space (121T) of the nozzle body (121a, 121b).
[0079] Through this, large impurities (polymer aggregates, fine metal particles) can be removed primarily before the filtering step, and polymer flow homogenization and dead zones can be prevented.
[0080] In the case of such sand (124), as high heat-resistant ceramic particles, it is made of aluminum oxide (Al2O3) or zirconia (ZrO2) and 2.5 g / cm³ 3 Up to 3.5 g / cm² 3 It is desirable to be filled with a density of
[0081] Next, the first nozzle part (123) is arranged so that its upper and lower surfaces are in contact with the first filter part (121), and is provided in the form of a plate having a plurality of first micro-movement holes that are open vertically to guide the downward movement of the polymer passing through the first filter part (121).
[0082] Consequently, the polymer that has passed through the first filter section (122) moves to the first nozzle section (123) located at the bottom, and the first nozzle section (123) serves to regulate the flow of the polymer and facilitate its transfer to the spinning process.
[0083] To this end, a plurality of first micro-movement holes provided in the first nozzle part (123) are provided with a diameter of 0.5 mm to 1.0 mm, and a coating treatment is performed using a first coating composition comprising 20 to 35 parts by weight of polytetrafluoroethylene (PTFE), 8 to 13 parts by weight of carbon nanotube (CNT), 10 to 14 parts by weight of hexafluoropropylene (HFP), 15 to 18 parts by weight of nano silica (Nano-SiO2), and 5 to 7 parts by weight of poly(hexamethylene dodecanediamide) on the inner wall to form a first coating film having a thickness of 2 μm to 4 μm.
[0084] Here, a coating treatment is performed on the inner wall of the moving hole of the first nozzle part (123) using the first coating composition to impart superhydrophobic and low-friction properties, thereby preventing adhesion of the polymer based on the first coating film and improving fluidity.
[0085] Polytetrafluoroethylene (PTFE) in this first coating composition has the function of significantly lowering the coefficient of friction and imparting extreme low friction characteristics, thereby preventing the molten polymer from adhering to the inner wall of the nozzle and maintaining a smooth flow; it is preferable to have an appropriate content range of 20 to 35 parts by weight.
[0086] This is because if less than 20 parts by weight of polytetrafluoroethylene (PTFE) is added to the first coating composition, low friction performance is not sufficiently secured, and conversely, if it exceeds 35 parts by weight, the coating film becomes thick, the inner diameter of the nozzle narrows, and fluidity may decrease.
[0087] In addition, carbon nanotubes (CNT) in the first coating composition are components that improve the mechanical strength of the coating layer, increase wear resistance, and impart conductivity to prevent electrostatic accumulation, and it is preferable to have an appropriate content range of 8 to 13 parts by weight.
[0088] This is because if carbon nanotubes (CNT) in the first coating composition are added in an amount of less than 8 parts by weight, the effect of strengthening wear resistance is not sufficiently secured, and conversely, if it exceeds 13 parts by weight, the aggregation of CNTs occurs, which may reduce the uniformity of the coating film.
[0089] In addition, hexafluoropropylene (HFP) in the first coating composition is a component that improves superhydrophobicity and chemical resistance to maximize the anti-sticking effect when the polymer comes into contact with the inner wall of the nozzle, and it is preferable to have an appropriate content range of 10 to 14 parts by weight.
[0090] This is because if hexafluoropropylene (HFP) is added in an amount of less than 10 parts by weight in the first coating composition, the superhydrophobic effect is not sufficiently expressed, and conversely, if it exceeds 14 parts by weight, the coating layer becomes excessively flexible, which may reduce wear resistance.
[0091] In addition, nano silica (Nano-SiO₂) in the first coating composition is a component that increases the density of the coating film and controls surface roughness to reduce friction and improve durability, and it is preferable to have an appropriate content range of 15 to 18 parts by weight.
[0092] This is because if nano-silica (Nano-SiO₂) is added in an amount of less than 15 parts by weight in the first coating composition, the mechanical strength of the coating film is not sufficiently secured, and conversely, if it exceeds 18 parts by weight, aggregation between silica particles occurs, which may reduce the uniformity of the coating layer.
[0093] Finally, poly(hexamethylene dodecanediamide) (PA612) in the first coating composition is a component that strengthens the adhesion between the coating film and the nozzle surface to prevent delamination and improve heat resistance, and it is preferable to have an appropriate content range of 5 to 7 parts by weight.
[0094] This is because if poly(hexamethylene dodecanediamide) (PA612) is added in an amount of less than 5 parts by weight in the first coating composition, sufficient adhesion is not secured, and there is a risk that the coating layer will easily peel off, while conversely, if it exceeds 7 parts by weight, the coating film becomes excessively flexible, which may reduce wear resistance.
[0095] The thickness of this first coating film is uniformly formed in the range of 2 μm to 4 μm, and high adhesion and durability are secured by applying Plasma Enhanced Chemical Vapor Deposition (PECVD) or a spray-plasma combined process.
[0096] Through this, the flow of the polymer is maintained smoothly on the inner wall of the moving hole of the first nozzle part (123), and contamination or blockage can be minimized even during long-term use.
[0097] In addition, the first nozzle section (123) not only guides the movement of the polymer but also performs the role of maintaining a uniform flow rate of the polymer to prevent pressure fluctuations from occurring in the subsequent filter and nozzle.
[0098] In particular, by releasing the polymer at a constant speed through each first micro-movement hole, the breakage phenomenon during the spinning process is minimized, and ultimately, uniform fiber quality can be maintained.
[0099] In this way, the first filter section (122), the sand layer (124), and the first nozzle section (123) each perform functions such as removing impurities, homogenizing flow, and reducing friction, thereby solving problems such as nozzle clogging, flow imbalance, and viscosity change that occurred in the conventional extrusion process, and consequently enabling the stable production of recycled polyester fibers of uniform quality while maximizing continuous productivity.
[0100] Next, the second filter section (125) is positioned so that the lower and upper surfaces of the first nozzle section (123) are in contact, and compared to the first filter section (122), the filter hole size is smaller and the number of meshes is larger, corresponding to a filter made of STS 316L material that supports the removal of small particles (fine polymer aggregates, dust, etc.) that are not filtered out in the first filtering and the maintenance of uniform viscosity.
[0101] The role of the second filter section (125) is to effectively remove small particles (fine polymer aggregates, dust, etc.) that are not removed in the first filtering, while simultaneously supporting the uniform maintenance of the polymer's viscosity. To this end, it is equipped with a filter hole size of 120 μm to 140 μm, and the filter hole is formed to a size of 80 mesh to 150 mesh.
[0102] In addition, the second filter section (125) is used in an environment requiring high heat resistance and wear resistance, so it is made of STS 316L (stainless steel) material and has strong chemical resistance, which can prevent corrosion or filter clogging that may occur during the polymer melting and extrusion process.
[0103] In particular, since a high pressure of 150 to 250 Bar is applied during polymer extrusion, it is composed of a multi-layer mesh filter to ensure a constant flow while maintaining the rigidity of the filter, and is designed to remove bubbles or microfine particles through the combination of filter layers.
[0104] In conjunction with this, the second nozzle part (126) is arranged so that its upper and lower surfaces are in contact with the second filter part (125), and is provided in the form of a plate having a plurality of second micro-movement holes that are open vertically to guide the downward movement of the polymer passing through the second filter part (125).
[0105] The second nozzle part (126) is provided with a plurality of second micro moving holes having a diameter of 0.2 mm to 0.5 mm and plays the most important role in maintaining viscosity balance. On the inner walls of the plurality of second micro moving holes provided in the second nozzle part (126), a coating treatment is performed using a second coating composition comprising 55 to 60 parts by weight of aluminum oxide, 15 to 19 parts by weight of silicon carbide; 7 to 9 parts by weight of yttria-stabilized zirconia (YSZ); and 12 to 14 parts by weight of poly(dimethylsiloxane), so that a second coating film having a thickness of 50 μm to 70 μm is formed.
[0106] In particular, a ceramic-based second coating composition having high heat resistance and wear resistance is applied to the inner walls of a plurality of second micro-movement holes provided in the second nozzle part (126), thereby optimizing the flow of the polymer and performing the function of preventing adhesion inside the nozzle.
[0107] This second coating composition consists of aluminum oxide, silicon carbide (SiC), yttria-stabilized zirconia (YSZ), and poly(dimethylsiloxane) (PDMS), and each component provides wear resistance, heat resistance, chemical stability, and surface modification properties.
[0108] Here, aluminum oxide in the second coating composition is a component that provides high-temperature stability and wear resistance, thereby protecting the inner wall of the nozzle from wear even during long-term use, preventing structural deformation caused by friction and pressure changes occurring in the extrusion environment, and maintaining the smooth flow of the polymer, and it is preferable to have an appropriate content range of 55 to 60 parts by weight.
[0109] This is because if the aluminum oxide in the second coating composition is prepared in an amount of less than 55 parts by weight, sufficient wear resistance is not ensured, and if it exceeds 60 parts by weight, the rigidity of the coating film increases, and there is a possibility that cracks may occur.
[0110] In addition, silicon carbide (SiC) in the second coating composition is a component that improves impact resistance and heat resistance and prevents surface damage caused by viscous friction during the movement of the polymer, and it is desirable to have an appropriate content range of 15 to 19 parts by weight.
[0111] This is because if silicon carbide (SiC) in the second coating composition is provided in an amount of less than 15 parts by weight, the durability of the coating film may be reduced, and conversely, if it exceeds 19 parts by weight, the coating layer may become excessively hard and vulnerable to impact.
[0112] In addition, yttria-stabilized zirconia (YSZ) in the second coating composition is a component that improves thermal shock resistance and prevents cracking and delamination caused by rapid temperature changes during polymer extrusion, and it is preferable to have an appropriate content range of 7 to 9 parts by weight.
[0113] This is because if the yttria-stabilized zirconia (YSZ) in the second coating composition is provided in an amount of less than 7 parts by weight, the thermal shock resistance is insufficient, and conversely, if it exceeds 9 parts by weight, the mechanical properties of the coating layer may be degraded.
[0114] Finally, poly(dimethylsiloxane), PDMS, in the second coating composition is a component that imparts superhydrophobicity and surface lubrication (Non-Stick & Lubrication), allowing the polymer to move smoothly without adhering to the inside of the nozzle, and it is preferable to have an appropriate content range of 12 to 14 parts by weight.
[0115] This is because if the polydimethylsiloxane (PDMS) in the second coating composition is provided in an amount of less than 12 parts by weight, the surface lubricity of the coating layer is not sufficiently secured, and conversely, if it exceeds 14 parts by weight, the coating layer becomes excessively flexible, which may reduce wear resistance.
[0116] As a result, the second coating composition is processed by plasma deposition or chemical vapor deposition (CVD) and is uniformly formed with a thickness of 50 μm to 70 μm.
[0117] This optimizes the density of the coating layer to maintain wear resistance while preventing it from becoming excessively hard, thereby simultaneously ensuring impact resistance and durability; additionally, the coating surface is processed into a microporous structure to maximize the retention of polymer viscosity and flow stability.
[0118] Next, the third filter section (127) is positioned so that the lower and upper surfaces of the second nozzle section (126) are in contact, and compared to the second filter section (125), the filter hole size is smaller and the number of meshes is larger to remove fine foreign substances or non-uniformity within the polymer that has passed through the first and second filtering, thereby maintaining an optimal condition for uniform fiber spinning.
[0119] Specifically, the third filter section (127) has a filter hole size of 20 μm to 50 μm to finally uniformly radiate the extruded molten polymer, and the filter hole is formed to a size of 300 mesh to 500 mesh.
[0120] In addition, the third filter section (127) is made of STS 316L (stainless steel) or a heat-resistant alloy material so that it can operate stably without deformation even in high temperature and high pressure environments.
[0121] In conjunction with this, the third nozzle part (128) is arranged so that its upper and lower surfaces are in contact with the third filter part (127), and is provided in the form of a plate having a plurality of third micro-movement holes that are open vertically to guide the downward movement of the polymer passing through the third filter part (127).
[0122] This third nozzle part (128) is provided with a plurality of third micro moving holes having a diameter of 0.2 mm to 0.5 mm, and on the inner wall of the third micro moving holes, a Diamond-Like Carbon (DLC) coating treatment is performed using Chemical Vapor Deposition (CVD) at a temperature of 250°C to 450°C and under vacuum conditions to form a third coating film having a thickness of 1 μm to 3 μm.
[0123] This DLC coating imparts extreme low friction properties to prevent adhesion during polymer movement and maximizes fluidity, enabling uniform spinning in the form of threads.
[0124] In addition, the DLC coating provides excellent wear resistance through a diamond-like carbon film structure, protecting the inner wall of the nozzle from wear even in high-speed spinning environments. Its superior oxidation resistance enables the maintenance of stable coating performance over a long period without chemical deformation caused by additives or gases within the polymer.
[0125] In the deposition process of this DLC coating, the CVD method is applied in a vacuum environment, and carbon-based elements are vaporized through plasma acceleration and uniformly deposited on the inner wall of the nozzle.
[0126] In particular, rotary plasma deposition technology is utilized to ensure that the coating layer is formed evenly, and the surface roughness (Ra) is maintained at 0.02 μm or less so that the emitted polymer can flow smoothly without frictional resistance.
[0127] This prevents clogging of the nozzle inner wall and enables the maintenance of uniform fiber quality even during a continuous spinning process.
[0128] Specifically, a Diamond-Like Carbon (DLC) coating is applied to the inner wall of the third micro-movement hole of the third nozzle part (128). To this end, the third coating composition, composed of a specific composition ratio, includes amorphous carbon (aC), hydrogen (H), silicon (Si), tungsten (W), and fluorine (F) to provide extreme low friction and wear resistance characteristics, allowing the polymer to move smoothly without sticking inside the nozzle, and to enhance heat resistance so that stable performance can be maintained even in a high-temperature environment for a long time.
[0129] Amorphous carbon (aC), a key component of the third coating composition, forms the basic structure of the DLC coating layer and acts as an important factor in imparting ultra-low friction and wear resistance characteristics.
[0130] This allows the DLC coating layer to maintain a flexible structure while possessing strength similar to diamond, ensuring it remains stable without cracking even in high-temperature and high-pressure environments.
[0131] This amorphous carbon is applied in the range of 60 to 75 parts by weight. If less than 60 parts by weight is added, the strength of the DLC coating layer may be insufficient, which may reduce wear resistance, while if more than 75 parts by weight is added, the coating layer may become excessively hard, increasing the likelihood of cracking.
[0132] In addition, hydrogen (H) plays a role in relieving internal stress within the DLC coating layer and lowering surface energy to maximize the superhydrophobicity effect.
[0133] This is a key factor in preventing the polymer from adhering to the inner wall of the nozzle and is applied in a range of 10 to 20 parts by weight; if the hydrogen content is less than 10 parts by weight, the superhydrophobic effect is not sufficiently exhibited, and conversely, if it exceeds 20 parts by weight, the mechanical strength of the DLC coating layer decreases, which may reduce wear resistance.
[0134] In addition, silicon (Si) improves the heat resistance and oxidation resistance of the DLC coating layer and plays a role in increasing the mechanical stability of the coating layer, thereby enabling the DLC coating to maintain stable performance even in high-temperature environments, and is applied in a range of 5 to 10 parts by weight.
[0135] This is because if the silicon content is less than 5 parts by weight, the heat resistance of the DLC coating layer is insufficient, and if it exceeds 10 parts by weight, there is a possibility that the mechanical properties of the coating layer will deteriorate.
[0136] In addition, tungsten (W) plays a role in improving the wear resistance and hardness of the DLC coating layer and increasing crack resistance. This enables the DLC coating layer to maintain stable performance for a long period without wearing out, especially in environments where polymers are ejected at high speeds.
[0137] Such tungsten is applied in a range of 5 to 8 parts by weight; if less than 5 parts by weight, the wear resistance of the coating layer may not be sufficient, and conversely, if more than 8 parts by weight, the coating layer may become excessively hard, increasing the likelihood of cracking.
[0138] Finally, fluorine (F) plays a role in imparting superhydrophobic and anti-adhesion properties to the DLC coating layer and provides a function to prevent surface contamination.
[0139] This allows the polymer to be discharged smoothly without adhering to the inner wall of the nozzle, and is applied in the range of 3 to 7 parts by weight. If the fluorine content is less than 3 parts by weight, the superhydrophobic effect may not be sufficient, and conversely, if it exceeds 7 parts by weight, the mechanical strength of the coating layer may decrease, potentially leading to reduced durability.
[0140] This third coating composition is applied in a vacuum environment using the CVD (Chemical Vapor Deposition) method, and a DLC coating layer is formed by vaporizing carbon and other elements using plasma.
[0141] In this process, rotational plasma deposition technology is applied to ensure that the coating layer is formed uniformly, and the surface roughness is maintained at a level of Ra ≤ 0.02μm to ensure that thread-shaped spinning is carried out smoothly.
[0142] This prevents adhesion inside the nozzle and allows the wear resistance and heat resistance of the DLC coating layer to be maintained even during long-term use.
[0143] And above all, the third nozzle section (128) is designed in the shape of a tapered horn with a cross-sectional area that decreases as it goes downward, as shown in FIG. 2, and through this, the flow rate is accelerated and the viscosity of the polymer is maintained at a constant level, making it possible to spin out a uniform thread-like form.
[0144] This tapered structure optimizes pressure as the polymer is gradually compressed, allowing the yarn to maintain a uniform diameter and minimizing yarn breakage.
[0145] Specifically, the third nozzle section (128) is designed in the shape of a tapered horn with a cross-sectional area that decreases as it goes downward, thereby allowing the molten polymer to be gradually compressed, the flow velocity to be accelerated, and the viscosity to be maintained uniformly. This tapered structure is designed to utilize the Venturi Effect, in which the flow velocity naturally increases as the polymer moves along a narrowing flow path, thereby stabilizing the flow of the polymer immediately before spinning and enabling uniform spinning in the form of threads.
[0146] In a tapered structure, the cross-sectional area of the path through which the polymer moves is gradually reduced, so the flow resistance is optimized and the internal pressure is maintained uniformly, allowing for a constant flow rate to be maintained during actual spinning.
[0147] In addition, since flow instability may occur when the cross-sectional area is rapidly reduced when the polymer is extruded, the third nozzle part (128) is adjusted to allow for gradual pressure changes by applying a tapered structure designed at a specific angle, so that the polymer is not subjected to excessively high shear stress during the compression process, while also allowing the actual discharge rate to be controlled.
[0148] These structural features play a key role in maintaining the uniformity of the diameter when the yarn is spun. When the molten polymer is extruded through the nozzle, if the tapered structure is not applied, turbulent flow occurs during the extrusion process, making it highly likely that the diameter of the yarn will not be uniform. However, if the tapered structure is applied, the polymer is compressed and has an aligned flow pattern, allowing for flow balance to be achieved so that the diameter of the yarn can be maintained uniformly.
[0149] This third nozzle part (128) is precisely joined to the lower cover part (121b) having an outlet (121b) and performs the role of optimizing the flow so that the extruded polymer can be smoothly discharged in the form of a thread.
[0150] In this regard, the lower cover portion (121b) is designed to maintain a uniform polymer flow immediately before spinning and supports the thread being emitted to have constant tension through air pressure control inside.
[0151] (4) Cooling and stretching treatment steps<S140, D단계>
[0152] In this step, a process is carried out to prepare recycled polyester fibers by cooling the polymer, which is extruded in the form of a thread through an extrusion nozzle unit via the melt extrusion treatment step (S130) performed earlier, to a temperature of 15°C to 25°C and then stretching it at a draw ratio of 1.5 to 3.5.
[0153] This process involves cooling and stabilizing the polymer spun into a thread form, followed by applying tensile force at a constant draw ratio to impart mechanical strength and elasticity, thereby enabling the securing of longitudinally uniform fiber quality.
[0154] Since the spun polymer yarn initially has a high temperature and is in a viscous state, an appropriate cooling process is essential to form a stable fiber structure. To this end, the present invention applies a cooling temperature of 15°C to 25°C, which is set as an optimal range to ensure that the molten polymer does not suddenly solidify and can crystallize uniformly.
[0155] In the cooling process, air quenching or water quenching methods may be applied, and in the present invention, the air quenching method is preferred to ensure uniform cooling.
[0156] Here, in the air cooling method, the spun yarn is rapidly cooled with air at a constant temperature to control the crystallization rate, thereby inducing the uniform formation of the fiber's internal structure.
[0157] In particular, by precisely controlling the flow rate and temperature of the cooling air, it prevents the yarn from becoming brittle or excessive internal stress from forming due to excessive rapid cooling, and ensures that it possesses consistent strength.
[0158] The cooled polymer yarn undergoes a drawing process to secure the final physical properties of the fiber, and the spun yarn is stretched with a constant tension to increase the molecular alignment of the polymer and improve the mechanical strength and elasticity of the fiber.
[0159] In the present invention, a draw ratio of 1.5 to 3.5 is applied, which is set to a range that can maintain optimal strength and elasticity.
[0160] The draw ratio indicates how much the length of the fiber increases compared to the initial length. If the draw ratio is low, the strength of the fiber may be insufficient, and conversely, if the draw ratio is too high, the fiber may be excessively stretched, potentially causing internal cracks or becoming brittle. Therefore, a draw ratio of 1.5 to 3.5 is applied so that the fiber can maintain a uniform diameter and structure while having appropriate tensile strength and elasticity.
[0161] In addition, the temperature and speed of the stretching process also act as important variables, playing a role in adjusting the final physical properties by controlling the crystallization rate of the fibers.
[0162] In this regard, the stretching temperature is generally set in a range higher than the glass transition temperature (Tg) of polyester, and in the present invention, it can be controlled in the range of 50°C to 90°C to maintain an optimal stretching environment.
[0163] In addition, the fibers after the stretching process are collected in their final form through a winding process, during which the fiber tension is adjusted to maintain a consistent diameter and structure.
[0164] In addition, if necessary, a heat setting process can be additionally applied to improve the shape stability of the fibers and enhance processability in subsequent processes.
[0165] In conclusion, in this step, the spun yarn is uniformly solidified through an appropriate cooling process, and then mechanical strength and elasticity are imparted through stretching treatment to complete the final recycled polyester fiber.
[0166] Through this, uniform fiber quality can be secured compared to existing processes, and the durability and processability of the fibers can be simultaneously improved by optimizing the draw ratio and cooling conditions.
[0167] 2. Explanation of the effect test of the product resulting from the recycled polyester fiber manufacturing method
[0168] For the product manufactured by the method of manufacturing recycled polyester fibers using a melt extrusion device (100) equipped with a thermal extrusion nozzle unit (120) according to the present invention, the friction coefficient of the nozzle inner wall, the flow rate of the polymer, the defect rate, the number of cleaning cycles, and the flow rate uniformity were evaluated by varying various conditions in the manufacturing method as described below, and the following experimental methods were used for the purpose of defining properties, etc., by means that are obvious to technicians in the art.
[0169] (1) Preparation of the example
[0170] - Example 1
[0171] First, as previously explained, the extrusion nozzle unit (120) of the melt extrusion device (100) is stacked and arranged in the order of sand (124) - first filter section (122) - first nozzle section (123) - second filter section (125) - second nozzle section (126) - third filter section (127) - third nozzle section (128) in the installation space (121T) within the nozzle body (121a, 121b) from top to bottom.
[0172] And the first filter section (122) is a filter made of STS 316L material with a filter hole size of 300 μm and a mesh count of 60, the first nozzle section (123) has a plurality of first fine moving holes with a diameter of 0.8 mm, and the sand layer (124) is a polymer sand made of aluminum oxide material with an average particle size of 300 μm and 3.2 g / cm³ 3 It has a density of.
[0173] In addition, the inner wall of the first micro-movement hole of the first nozzle part (123) is treated with a superhydrophobic coating using a first coating composition comprising 27 parts by weight of polytetrafluoroethylene (PTFE), 10 parts by weight of carbon nanotubes (CNT), 12 parts by weight of hexafluoropropylene (HFP), 16 parts by weight of nano silica (SiO₂), and 6 parts by weight of poly(hexamethylene dodecanediamide), thereby forming a first coating film with a thickness of 3 μm.
[0174] Next, the second filter section (125) is a filter made of STS 316L material with a filter hole size of 130 μm and 120 mesh counts, and the second nozzle section (126) has a plurality of second fine moving holes with a diameter of 0.3 mm.
[0175] In addition, the inner wall of the second micro-movement hole of the second nozzle part (125) is treated with a ceramic heat-resistant coating using a second coating composition comprising 58 parts by weight of aluminum oxide, 17 parts by weight of silicon carbide (SiC), 8 parts by weight of yttria-stabilized zirconia (YSZ), and 13 parts by weight of polydimethylsiloxane (PDMS), thereby forming a second coating film with a thickness of 60 μm.
[0176] Finally, the third filter section (127) is a filter made of STS 316L material with a filter hole size of 40 μm and 4000 mesh counts, and the third nozzle section (128) has a plurality of third fine moving holes with a diameter of 0.4 mm.
[0177] In addition, the inner wall of the third micro-movement hole of the third nozzle part (127) is treated with a third coating composition comprising 70 parts by weight of amorphous carbon (aC), 15 parts by weight of hydrogen (H), 7 parts by weight of silicon (Si), 6 parts by weight of tungsten (W), and 5 parts by weight of fluorine (F) to form a third coating film with a thickness of 2 μm by applying a DLC coating (Diamond-Like Carbon).
[0178] And the third nozzle part (128) is designed in the shape of a tapered horn with a cross-sectional area that decreases as it goes downward.
[0179] An extrusion nozzle unit (120) within a melt extrusion device (100) having such a configuration and compositional and structural features is used as Example 1.
[0180] - Example 2
[0181] As Example 2, an extrusion nozzle unit (120) within a melt extrusion device (100) is used, which maintains the same configuration and compositional and structural features as Example 1, but with respect to the structure of one third nozzle part (128), is provided in a plate shape with no change in cross-sectional area by height, rather than a tapered horn shape in which the cross-sectional area decreases as it goes downward.
[0182] - Example 3
[0183] An extrusion nozzle unit (120) within a melt extrusion device (100) is used as Example 3, which maintains the same configuration and compositional and structural features as Example 1, but has the difference in that a first coating film of 3 μm thickness is not formed by applying a superhydrophobic coating to the inner wall of the first micro-moving hole of one first nozzle part (123) through the first coating composition.
[0184] - Example 4
[0185] An extrusion nozzle unit (120) within a melt extrusion device (100) is used as Example 4, which maintains the same configuration and compositional and structural features as Example 1, but differs in that a second coating film with a thickness of 60 μm is not formed by treating the inner wall of the second micro-moving hole of one second nozzle part (126) with a ceramic heat-resistant coating through the second coating composition.
[0186] - Example 5
[0187] As Example 5, an extrusion nozzle unit (120) within a melt extrusion device (100) is used, which maintains the same configuration and compositional and structural features as Example 1, but differs in that a third coating film of 2 μm thickness is not formed by treating the inner wall of the third micro-moving hole of one third nozzle part (128) with a DLC coating (Diamond-Like Carbon) through a third coating composition.
[0188] Various evaluations presented below are conducted using each of the Examples 1 to 5 prepared as described above, provided that all processes of the method for manufacturing recycled polyester fibers are carried out under the same conditions and in the same manner.
[0189] Specifically, waste fibers (polyester fabric) and waste plastics (PET bottles, films) are sorted to have a foreign matter content of 1% by weight or less, and then mechanical stirring washing (rotation speed 300 rpm) is performed at 60°C for 15 minutes using an alkaline detergent (sodium hydroxide NaOH 0.5 wt%).
[0190] Next, after grinding with a high-speed rotating blade at a rotational speed of 5000 rpm, hydrogen peroxide treatment and ultrasonic (40 kHz) treatment are carried out at 80°C for 30 minutes to allow de-dyeing to proceed.
[0191] After such de-dyeing treatment, DI (deionized) water washing is performed at 70°C for 10 minutes, followed by hot air drying at 100°C for 2 hours so that the final moisture content becomes 0.1% by weight or less.
[0192] Next, the strands produced by melt extrusion at 280°C and 200 bar at a screw rotation speed of 50 rpm are pelletized into chip form with an average diameter of 3 mm to prepare recycled polyester chips.
[0193] Next, a molten polymer having a polymer viscosity (IV) of 0.62 dL / g at 280°C and 200 bar is prepared through a melting treatment unit (110) in a melting extrusion device (100) and introduced into an inlet (121H) provided on the upper part of each embodiment's nozzle body (121a, 121b) at a flow rate of 5 mL / s.
[0194] In each embodiment, the extrusion nozzle unit (120) of the melt extrusion device (100) is passed through, and the extrusion process is carried out at a spinning speed of 2500 m / min with a spinning temperature and pressure of 275°C and 180 bar, and several measurements are taken during this process.
[0195] Furthermore, several measurements are taken on the resulting product after the extruded polymer in the form of a thread is subjected to air quenching treatment at a cooling temperature of 20°C and a cooling air flow rate of 5 m / s, followed by a drawing treatment at a drawing speed of 5000 m / min and a drawing temperature of 80°C with a draw ratio of 2.8.
[0196] (2) Measurement of Friction Coefficient and Flow Rate
[0197] In the process of carrying out the method for manufacturing recycled polyester fibers using the extrusion nozzle unit (120) of the melt extrusion device (100) of Examples 1 to 5 prepared as described above, the frictional force between the polymer and the inner wall of the first micro-movement hole of the first nozzle part (123) and the inner wall of the third micro-movement hole of the third nozzle part (128), respectively, was directly measured using a Pin-on-Disk Tribometer based on ASTM G99, and the results are as shown in Table 1 below.
[0198] The specific test conditions are as follows.
[0199] - Load: 5N
[0200] - Rotation speed: 10 mm / s
[0201] - Experiment time: 60 seconds
[0202] - Environmental conditions: 280℃, 200 bar
[0203] - Formula for calculating the coefficient of friction (μ): Coefficient of friction (μ) = F / N (F: Measured friction force (N), N: Acting normal load (5N))
[0204] Next, during the process of manufacturing recycled polyester fibers using the extrusion nozzle unit (120) of the melt extrusion device (100) of Examples 1 to 5, the flow rate (ml / s) of the extruded polymer moving along the inner wall of the third micro-movement hole of the third nozzle part (128) for each example was measured in real time using a high-speed flow sensor (Flowmeter, Digital Mass Flow Sensor), and the levels of the mutual result values were organized into relative ratios, and the results are as shown in Table 1 below.
[0205] First micro-moving Hall friction coefficient (μ) Third micro-moving Hall friction coefficient (μ) 3rd micro-movement hole internal flow velocity (relative value) Example 1 0.25 0.20 130% Example 2 0.26 0.23 110.5% Example 3 0.36 0.20 117% Example 4 0.25 0.21 122% Example 5 0.26 0.30 104%
[0206] As shown in Table 1, Example 1 exhibited the most desirable performance, and through the application of a superhydrophobic coating on the first nozzle part, a DLC coating on the third nozzle part, and a tapered structure, it showed the effect of increasing the internal flow velocity by up to 130% while maintaining the friction coefficients at 0.25 and 0.20, respectively.
[0207] On the other hand, in Example 5, where the DLC coating was removed, the friction coefficient increased to 0.30 and the flow rate decreased sharply to 104%, causing radiation imbalance; in the case of Example 3, which did not have a superhydrophobic coating, the friction coefficient also increased to 0.36 and the flow rate decreased to 117%, showing a tendency for the polymer adhesion phenomenon to be prominent.
[0208] In addition, in the case of Example 2, where the tapered structure was removed, the friction coefficient increased to 0.23 and the flow velocity decreased to 110.5%, proving that the tapered structure plays an important role in accelerating the flow and maintaining flow uniformity.
[0209] In summary, these results suggest that a combination of superhydrophobic coating, DLC coating, and tapered structure is essential to maintain smooth polymer flow on the inner wall of the nozzle, and if any of these are removed, friction increases and flow velocity decreases, which is likely to degrade the spinning quality.
[0210] In particular, when the DLC coating is removed, friction increases most significantly, causing a rapid decrease in internal flow velocity; however, when the tapered structure is removed, a decrease in flow velocity occurs, resulting in a problem of reduced flow uniformity within the nozzle. Through this, it was experimentally verified that for an optimized nozzle design, a configuration like Example 1, which simultaneously ensures friction reduction and flow velocity uniformity, is required.
[0211] (3) Measurement of defect rate and flow rate
[0212] As previously explained, a method for manufacturing recycled polyester fibers was carried out using the extrusion nozzle unit (120) of the melt extrusion device (100) of Examples 1 to 5 prepared as described above. After sampling 100 of each recycled polyester fiber prepared for each example, the number of fibers with defects was counted and the defect rate (%) was calculated, and the results are as shown in Table 2 below.
[0213] Next, a method for manufacturing recycled polyester fibers was carried out continuously for 24 hours using the extrusion nozzle unit (120) of the melt extrusion device (100) of Examples 1 to 5 prepared as described above, and cleaning was performed whenever the nozzle became clogged or its performance deteriorated by checking the internal contamination level of the nozzle, and the number of times cleaning was required in at least one of the first nozzle part (123) to the third nozzle part (128) was recorded, and the results are as shown in Table 2 below.
[0214] Defect rate (%) Cleaning frequency (times / day) Example 1 2.1 1-2 Example 2 3.9 3-4 Example 3 3.4 4 Example 4 2.8 3-4 Example 5 4.6 4-5
[0215] As shown in Table 2, Example 1 recorded the lowest defect rate (2.1%) and the minimum number of cleaning cycles (1-2 times / day), which demonstrates that the application of superhydrophobic coating, ceramic heat-resistant coating, and DLC coating played an effective role in minimizing internal nozzle adhesion and maintaining radiation uniformity.
[0216] On the other hand, Example 5, in which the DLC coating was removed, showed the highest defect rate of 4.6% and the number of cleaning cycles increased to 4-5 times / day, indicating that polymer adhesion and clogging within the nozzle occurred most severely. Example 2, in which the tapered structure was removed, also showed a tendency for the spinning quality to deteriorate due to reduced flow uniformity, with an increase in the defect rate (3.9%) and cleaning frequency (3-4 times / day).
[0217] In summary, these results indicate that a design like Example 1, which combines a superhydrophobic coating, a DLC coating, and a tapered structure, is essential to optimize the failure rate and maintenance efficiency. In particular, it was confirmed that when the DLC coating is removed, polymer adhesion intensifies, leading to a rapid increase in the failure rate and the number of cleaning cycles.
[0218] In addition, in Example 3 (defect rate 3.4%, cleaning 4 times / day) in which the superhydrophobic coating was removed, there was a tendency for increased adhesion due to internal nozzle contamination, and in the case of Example 4 (defect rate 2.8%, cleaning 3 to 4 times / day) in which the ceramic heat-resistant coating was removed, it suggests that long-term performance degradation may be a concern in terms of maintaining nozzle durability rather than friction reduction.
[0219] (4) Flow Uniformity Measurement
[0220] In the process of carrying out a method for manufacturing recycled polyester fibers using the extrusion nozzle unit (120) of the melt extrusion device (100) of Examples 1 to 5 prepared as described above, the flow rate was measured at 10-second intervals for 1 hour from the moment the polymer was first extruded after being fed into the extrusion nozzle unit (120) using a digital flow sensor (Mass Flow Meter, Digital Precision Flow Sensor) (calculated after a total of 360 measurements and an average value was calculated) to calculate the standard deviation (SD) of the measurement data and confirm uniformity, and the results are as shown in Table 3 below.
[0221] - Flow rate uniformity (%) = [1 - (σ / μ)] × 100
[0222] -σ (standard deviation): standard deviation of flow rate fluctuation values
[0223] -μ (average value): Average flow rate measured over 1 hour
[0224] Flow rate uniformity (%) Thread diameter variation range (±%) Example 1 98 0.5 Example 2 90 2.5 Example 3 91 2.2 Example 4 93 1.7 Example 5 82 4.0
[0225] As shown in Table 3, Example 1 recorded the highest flow rate uniformity (98%) and minimized the range of yarn diameter variation (±0.5%), indicating that it maintained the most stable spinning quality. This implies that the combination of superhydrophobic coating, DLC coating, and tapered structure contributed to maintaining smooth polymer flow and achieving uniform spinning.
[0226] On the other hand, Example 5, in which the DLC coating was removed, showed the most severe spin imbalance with flow uniformity decreasing to 82% and the range of variation in diameter increasing to ±4.0%, and Example 2, in which the tapered structure was removed, also showed a decrease in flow uniformity to 90% and the range of variation in diameter increasing to ±2.5%, confirming the effect of reduced flow acceleration.
[0227] In summary, these results indicate that to optimize spinning quality, it is essential to maximize flow uniformity and minimize the range of variation in thread diameter. To achieve this, it was confirmed that a design such as Example 1, which includes a superhydrophobic coating, a DLC coating, and a tapered structure, is the most effective.
[0228] In particular, in Example 5, where the DLC coating was removed, the flow rate fluctuations were intensified due to increased friction and the yarn diameter deviation was the largest, resulting in a noticeable deterioration in quality. In Example 3, where the superhydrophobic coating was removed (flow rate uniformity 91%, yarn diameter variation range ±2.2%), the spinning uniformity also tended to deteriorate due to adhesion.
[0229] In addition, Example 4 (flow rate uniformity 93%, thread diameter variation range ±1.7%), in which the ceramic heat-resistant coating was removed, has concerns regarding long-term durability degradation, and through this, it was proven that friction reduction and flow rate uniformity must be achieved simultaneously to ensure spinning quality.
[0230] The embodiments disclosed in this invention are intended to illustrate, not limit, the technical concept of the invention, and the scope of the technical concept of the invention is not limited by these embodiments. The scope of protection shall be interpreted by the claims below, and all technical concepts within an equivalent scope shall be interpreted as being included within the scope of rights of this invention. Explanation of the symbols
[0231] 100 : Melting extrusion device 110 : Melting unit 120 : Extrusion nozzle unit 121a, 121b: Nozzle body 122 : 1st filter section 123 : First nozzle section 124: Sand 125 : 2nd filter section 126 : Second nozzle section 127 : 3rd filter section 128 : 3rd nozzle section
Claims
Claim 1 Step A, which involves treating waste fibers and waste plastics that have been sorted, washed, and crushed, and then subjecting them to decolorization followed by washing and drying; Step B, which involves melt-extruding the subject that has undergone decolorization, washing, and drying in Step A under conditions of a temperature of 250°C to 300°C and a pressure of 150 Bar to 250 Bar, and then pelletizing the resulting strands into chip form to prepare recycled polyester chips; and Step C, wherein the recycled polyester chips prepared through Step B are dried, fed into a melt extrusion device, and the polymer converted into a molten state through heat treatment under conditions of a temperature of 270°C to 290°C and a pressure of 150 Bar to 250 Bar is fed into an extrusion nozzle unit provided in the melt extrusion device, undergoes a plurality of filtering treatments, and is spun into a thread form; wherein the extrusion nozzle unit provided in the melt extrusion device used through Step C comprises: a nozzle body having a predetermined installation space inside and an inlet port at the top for feeding a molten polymer; a first filter part disposed on the upper part of the nozzle body; a plate-shaped first nozzle part disposed so that the lower and upper parts of the first filter part are in contact, and having a plurality of first micro-movement holes open vertically to guide the downward movement of the polymer passing through the first filter part; and a 200μm Sand having a particle size of up to 400 μm; a second filter part arranged so that the lower and upper surfaces of the first nozzle part are in contact, and having a filter hole size smaller and a mesh count larger than that of the first filter part; a plate-shaped second nozzle part arranged so that the lower and upper surfaces of the second filter part are in contact, and having a plurality of second micro-movement holes open vertically to guide the downward movement of the polymer passing through the second filter part;A method for manufacturing recycled polyester fibers using a melt extrusion device equipped with an extrusion nozzle unit, comprising: a third filter section arranged so that the lower and upper surfaces of the second nozzle section are in contact, wherein the filter hole size is smaller and the number of meshes is larger compared to the second filter section; and a plate-shaped third nozzle section arranged so that the lower and upper surfaces of the third filter section are in contact, and having a plurality of third micro-movement holes open vertically to guide the downward movement of the polymer passing through the third filter section; wherein the third nozzle section is provided in a tapered truncated cone shape with a cross-sectional area that decreases as it extends downward. Claim 2 A method for manufacturing recycled polyester fibers using a melt extrusion device equipped with an extrusion nozzle unit, characterized in that, in claim 1, a Diamond-Like Carbon (DLC) coating treatment is performed on the inner walls of a plurality of third micro-moving holes provided in the third nozzle part using Chemical Vapor Deposition (CVD) at a temperature of 250°C to 450°C and under vacuum conditions, thereby forming a third coating film having a thickness of 1 μm to 3 μm. Claim 3 In claim 1, the first filter portion has a filter hole size of 200 μm to 400 μm and the filter holes are formed to a size of 50 mesh to 80 mesh, the first nozzle portion is provided with a plurality of first micro-moving holes having a diameter of 0.5 mm to 1.0 mm, and a coating treatment using a first coating composition comprising 20 to 35 parts by weight of polytetrafluoroethylene (PTFE), 8 to 13 parts by weight of carbon nanotube (CNT), 10 to 14 parts by weight of hexafluoropropylene (HFP), 15 to 18 parts by weight of nano-silica (Nano-SiO2), and 5 to 7 parts by weight of poly(hexamethylene dodecanediamide) is performed on the inner walls of the plurality of first micro-moving holes provided in the first nozzle portion. A method for manufacturing recycled polyester fibers using a melt extrusion device equipped with an extrusion nozzle unit, characterized by forming a first coating film having a thickness of 2 μm to 4 μm. Claim 4 In paragraph 3, the second filter portion has a filter hole size of 120 μm to 140 μm and the filter holes are formed to a size of 80 mesh to 150 mesh, the second nozzle portion is provided with a plurality of second micro-moving holes having a diameter of 0.2 mm to 0.5 mm, and the inner walls of the plurality of second micro-moving holes provided in the second nozzle portion contain 55 to 60 parts by weight of aluminum oxide, 15 to 19 parts by weight of silicon carbide; and 7 to 9 parts by weight of yttria-stabilized zirconia (YSZ). A method for manufacturing recycled polyester fibers using a melt extrusion device equipped with an extrusion nozzle unit, characterized in that a coating treatment is performed using a second coating composition comprising 12 to 14 parts by weight of poly(dimethylsiloxane), and a second coating film having a thickness of 50 μm to 70 μm is formed. Claim 5 A method for manufacturing recycled polyester fibers using a melt extrusion device equipped with an extrusion nozzle unit, wherein, in claim 4, the third filter part has a filter hole size of 20 μm to 50 μm and the filter hole is formed to a size of 300 mesh to 500 mesh, and the third nozzle part is provided with a plurality of third fine moving holes having a diameter of 0.2 mm to 0.5 mm. Claim 6 In claim 4, the method for manufacturing recycled polyester fibers using a melt extrusion device equipped with an extrusion nozzle unit is characterized by further including a step D in which a polymer extruded in the form of a yarn through the extrusion nozzle unit via step C is cooled to a temperature of 15°C to 25°C and then stretched at a draw ratio of 1.5 to 3.5 to produce recycled polyester fibers.